2016
DOI: 10.1002/cctc.201600397
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Large‐Scale Ultrathin Graphitic Carbon Nitride Nanosheets by a Hydrogen‐Bond‐Assisted Strategy for Improved Photocatalytic Hydrogen Production and Ciprofloxacin Degradation Activity

Abstract: Two‐dimensional nanosheets have attracted attention because of their fascinating properties in areas such as photocatalysis, sensors, and energy storage. Herein, a facile hydrogen‐bond‐assisted approach was designed to prepare graphitic carbon nitride (g‐C3N4) with large‐scale ultrathin nanosheets. Compared with previous methods, this method is simple, economical, and eco‐friendly. The as‐prepared ultrathin g‐C3N4 nanosheets have a few‐layer thickness of 2–3 nm and exhibit a significantly enhanced photocatalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…To date, some strategies have been used to overcome the above drawback. For example, nanoscaling, doping, surface modification and coupling with other semiconductor photocatalysts…”
Section: Introductionmentioning
confidence: 99%
“…To date, some strategies have been used to overcome the above drawback. For example, nanoscaling, doping, surface modification and coupling with other semiconductor photocatalysts…”
Section: Introductionmentioning
confidence: 99%
“…Compared with BCN, the peak intensity of the CNNS at 27.41 was weakened, which indicated that the g-C 3 N 4 nanosheets were obtained as expected. 26 In order to investigate the textural structures of the BCN and CNNS, nitrogen adsorption-desorption isotherms were measured and displayed. 27,28 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Polyethylene glycol (PEG) can act as a model structure directing template because of its low cost, low toxicity, relative stability, environmental friendliness, and uniform and well-ordered chain structure. Its ether oxygen forms week hydrogen bonds with melamine that could be exploited to prepare a controlled, well-structured, and self-assembled porous thin nanosheets . Thermal condensation of melamine began in the range of 300–350 °C, whereas PEG oxidized and decomposed to carbonaceous gases at 480 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Its ether oxygen forms week hydrogen bonds with melamine that could be exploited to prepare a controlled, well-structured, and self-assembled porous thin nanosheets. 26 Thermal condensation of melamine began in the range of 300−350 °C, whereas PEG oxidized and decomposed to carbonaceous gases at 480 °C. PEG and carbonaceous gases may prevent the complete stacking of g-C 3 N 4 intermediates compounds, which may result in the formation of porous thin sheets of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%